Unraveling the Contribution of High Temperature Stage to Jiang-Flavor Daqu, a Liquor Starter for Production of Chinese Jiang-Flavor Baijiu, With Special Reference to Metatranscriptomics - Yi, Zhuolin; Jin, Yanling; Xiao, Yao; Chen, Lanchai; Tan, Li; Du, Anping; He, Kaize; Liu, Dayu; Luo, Huibo; Fang, Yang; Zhao, Hai (Frontiers in Microbiology, 2019)
Jiang-flavor (JF) daqu is a liquor starter used for production of JF baijiu, a well-known distilled liquor in China. Although a high temperature stage (70 °C) is necessary for qualifying JF daqu, little is known regarding its active microbial community and functional enzymes, along with its role in generating flavor precursors for JF baijiu aroma. In this investigation, based on metatranscriptomics, fungi, such as Aspergillus and Penicillium, were identified as the most active microbial members and 230 carbohydrate-active enzymes were identified as potential saccharifying enzymes at 70 °C of JF daqu. Notably, most of enzymes in identified carbohydrate and energy pathways showed lower expression levels at 70 °C of JF daqu than those at the high temperature stage (62 °C) of Nong-flavor (NF) daqu, indicating lowering capacities of saccharification and fermentation by high temperature stage. Moreover, many enzymes, especially those related to the degradation of aromatic compounds, were only detected with low expression levels at 70 °C of JF daqu albeit not at 62 °C of NF daqu, indicating enhancing capacities of generating special trace aroma compounds in JF daqu by high temperature stage. Additionally, most of enzymes related to those capacities were highly expressed at 70 °C by fungal genus of Aspergillus, Coccidioides, Paracoccidioides, Penicillium and Rasamsonia. Therefore, this study not only sheds light on the crucial functions of high temperature stage but also paves the way to improve the quality of JF baijiu and provide active community and functional enzymes for other fermentation industries.